Богдан-Ігор Антонич: сецесія і контекст - Салига, Т. (Слово і Час, 2010)
Це роздуми про західноукраїнську поетичну сецесію перших десятиліть двадцятого століття, а
конкретніше ― про шлях сецесійного дискурсу в літпроцесі протяжністю від “Молодої музи” до творчої
практики Богдана-Ігоря Антонича (включаючи, звичайно, і її). Автор досліджує семантику кольорів і
музики в доантоничівський період, зіставляючи її з відповідною асоціативною навантаженістю образів
поета, який “жив колись на вишнях”. The author of the paper brings forward his refl ections on West-Ukrainian poetic Secession of the fi rst decades
of the 20th century, paying special attention to the place of Secession discourse within the literary process
which covers a wide range of literary phenomena, from “Moloda Muza” (“The Young Muse”) to Bohdan-Ihor
Antonych’s poetic heritage. In particular, the article analyses the semantics of colours and music before
Antonych and compares it with the associations called up by the visual and auditive metaphors of the poet
who “...used to live in the cherry trees”. Это размышления о западноукраинской поэтической
сецессии первых десятилетий двадцатого столетия,
а конкретнее ― о пути сецессионного дискурса в
литпроцессе протяженностью от “Молодой музы” до
творческой практики Богдана-Игоря Антонича (включая,
конечно, и её). Автор исследует семантику цвета и
музыки в предантоничевский период, сравнивая её с
соответственной ассоциативной наполненностью образов
поэта, который “жил когда-то на вишнях”.